Hubungan Antara Religiusitas Dengan Pemaafan Pada Siswa Muslim Di SMA Negeri 09 Kota Bekasi - Muzzamil, Ferdy; Supriadi, Tugimin; Alurmei, Wahyu Aulizalsini (Jurnal Ilmiah Wahana Pendidikan, 2024)
Relationship Between Religiosity and Forgiveness (Correlational Study of the Relationship between Religiosity and Forgiveness in Muslim Students in State High School 09 Bekasi City). This study aims to determine the relationship between religiosity and forgivenesss, while the subjects in this study are Muslim students at the State High School 09 Bekasi City. The technique used in this research is probability sampling technique with proportionate stratified random sampling. The subjects, from a population of 1069 students in the State High School 09 Bekasi City. This research method is quantitative research with correlational design. The results of the product moment analysis show that there is a significant positive relationship between religiosity and forgiveness of Muslim Students at the State High School 09 Bekasi City which is indicated by the correlation coefficient value of 0,606** with a significance of (p) of 0,000 < 0,05 (p≤0,05). This means that the higher the religiosity possessed by the individual, the higher the forgiveness possessed by that individual. Further researchers are advised to use new theories and other factors that are in accordance with future phenomena so that research is more representative.